Late Pleistocene/early Holocene tropical forest occupations at San Isidro and PeÑa Roja, Colombia - Gnecco, Cristóbal
Evidence of early occupations by hunter-gatherers in diverse tropical forests is increasing the world over (e.g. Gorman 1971; Pavlides & Gosden 1994), even in America (Roosevelt et al. 1996). This paper reports them in northern South America. Several lines of evidence suggest that many kinds of forests, some or all without modern analogues, existed in the American tropics during glacial times and remained there, with changing composition, until the present. According to evidence presented here, human beings adapted to those forests in northern South America since, at least, the end of the Pleistocene.